Thermal Effect on Bond Strength of Rubberized Concrete Filled Steel Tubular Sections (Fracture and Structural Integrity, 2020)
This study aims to assess the effect of high temperature on the bond strength of Concrete Filled Steel Tubular (CFST) sections incorporating crumb rubber particles as partial replacement of fine aggregates in concrete core. High daily temperatures; as in hot countries; was considered as well. Push out tests were conducted on 72 CFST specimens with five different concrete mixes. Prior to these tests, 210 concrete specimens were tested to obtain the mechanical properties of rubberized concrete under high temperature gradients. Some of the tests; on CFST sections or concrete specimens; were tested at the desired high temperature, and some others were tested after cooling down. The main variables considered were the crumb rubber replacement ratio, type of CFST section (circular or square) and temperature gradient. The test results indicated that high temperature reduces the bond strength between steel tube and rubberized concrete core with small percentage of rubber replacement. Recovery in bond strength was observed when the specimens were cooled down. Circular sections showed higher bond strength and ductility on its square counterpart.
Keywords: CFST sections; Bond Strength; Rubberized Concrete; Crumb Rubber; Elevated Temperature